Society of fear - Bude, Heinz (Cambridge Polity, 2018)
"From the rise of terrorism to the uncertainties associated with economic crisis and recession, our age is characterized by fear. Fear is the expression of a society on unstable foundations. Most of us feel that our social status is under threat and our future prospects in jeopardy. We are overwhelmed by a sense of having been catapulted into a world to which we no longer belong. Tracing this experience of fear, Heinz Bude uncovers a society marked by disturbing uncertainty, suppressed anger and quiet resentment. This is as true in our close relationships as it is in the world of work, in how we react to politicians as much as in our attitudes towards bankers and others in the financial sector. Bude shows how this fear is not derived so much from a 'powerful other' but rather from the seemingly endless range of possibilities which we face. While this may seem to offer us greater autonomy and freedom, in reality the unknown impact and meaning of each option creates a vacuum which is filled by fear. What conditions lead people to feel anxious and fearful for themselves and others? How can individuals withstand fear and develop ways of making their fears intelligible? Probing these and other questions, Bude provides a fresh analysis of some of the most fundamental features of our societies today"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Fear -- Social aspects